Ultrasound in endometrial cancer: evaluating the impact of pre-surgical staging - Rei, Mariana; Bernardes, João Francisco; Costa, Antónia (Oncology Reviews, 2025)
Preoperative staging in endometrial cancer has recently been implied as an important factor in accurately selecting low-risk cases, ultimately avoiding unnecessary lymph node debulking. Transvaginal ultrasound seems promising in clinical staging as it offers the possibility to assess the depth of myometrial infiltration and cervical stromal invasion. This commonly available, non-invasive, and low-cost modality serves as an accurate alternative to MRI, especially in middle- and low-income countries, where MRI may not be promptly available and cost is an important issue. This review aims to summarize the progressive role of clinical implementation of pelvic ultrasonography in the locoregional staging of endometrial carcinoma and to compare its accuracy with other preoperative methods.